Cartographies of deviation: interventions and symbolic disputes in “Espaço de Continuidade” (2016) and “La Bruja” (1981) - Coser, João Victor (Revista do Colóquio, 2025)
This article analyzes the relationships between collective memory and cultural heritage in contemporary art, using a comparative approach between two works: “Espaço de Continuidade” (2016), by João Cóser, and “La Bruja” (1981), by Cildo Meireles. Both explore the construction and resignification of public spaces, with an emphasis on public interaction and participation. The methodology applied consists of a qualitative and comparative analysis of the material and symbolic elements present in the artistic interventions. The results suggest that these artistic practices function as instruments for the preservation and transmission of cultural memory, connecting past and present, and reaffirming the potential of contemporary art as a living cultural legacy, capable of questioning the traditional limits of institutionalized art.
Keywords: collective memory, cultural heritage, contemporary art, artistic intervention